The Knowledge and Attitude Medical Surgical Nursing Relates to Alertness in Giving Care to Nursing COVID-19 Patients - Bakar, Abu; Sutejo, Sutejo; Ni'mah, Lailatn; Khatijah Lim, Abdullah * (Faculty of Medicine and Health Sciences, 2023)
Introduction: The purpose of this study was to analyze the relationship between the knowledge and attitudes of medical-surgical nurses and preparedness in providing nursing care for COVID-19 patients. The long COVID-19 pandemic has exhausted nurses serving patients, resulting in a lack of preparedness for health workers. Nurse preparedness is strongly influenced by the knowledge and attitudes of nurses in dealing with problems that arise. The preparedness, knowledge, and attitudes of nurses in providing nursing care for COVID-19 patients are not yet known in detail. Methods: The research design that has been used is cross-sectional. The population that has been used in this study is nurses in the Emergency Department. The sample that has been recruited is 34 people using the purposive sampling technique. The independent variables that have been determined are nurses' knowledge and attitudes about COVID-19. The dependent variable that has been used is the readiness of nurses in providing care about COVID-19. The instrument to collect data that has been used is a modified knowledge, attitude, and preparedness questionnaire. The data analysis that has been used is Spearman's rho correlation test. Results: The results showed that the knowledge and attitudes of medical-surgical nurses were related to nursing preparedness in providing nursing care to COVID-19 patients (p = 0.022 and p = 0.018). Conclusion: Nurses' knowledge and attitudes in providing nursing care to COVID-19 patients can maintain nurse preparedness properly. Training and seminars about COVID-19 are highly recommended to be carried out frequently so that nurse preparedness remains good.